Exploring anticancer activity of wild and polyploid mutant of Artemisia cina - Sri Kasmiyati; Elizabeth Betty Elok Kristiani; Maria Marina Herawati; Ferdy S Rondonuwu (Society for Indonesian Biodiversity, 2021)
Abstract. Kasmiyati S, Kristiani EBE, Herawati MM, Rondonuwu FS. 2021. Exploring anticancer activity of wild and polyploid mutant of Artemisia cina.  Biodiversitas 22: 1227-1234. The research aims were to explore the anticancer compounds in wild type (W) and polyploid mutant (P) of Artemisia cina Berg ex Poljakov using NIR and compare their cytotoxicity and selectivity on WiDR colon cancer and HTB183 lung cancer cell lines and Vero normal cell line. The W was obtained from B2P2TOOT Tawangmangu, Indonesia while P was by inducing A. cina shoot culture with 100 mg/l colchicine for 48 hours. They were extracted with hexane using the soxhletation method for 6 hours. The anticancer compounds were detected using NIR. The cytotoxic activity was determined using MTT assay, with Doxorubicin (D) as a control. The calculation of IC50 value used SPSS16 with a Probit analysis. The P contained the determined four compounds while the W contained no rutin. The IC50 values of W, P, and D were 295.5, 84.1, and 0.5 µg/mL on WiDr, 322.4, 128.6, and 39.9 µg/mL on HTB 183, whereas on Vero were 104, 315.6, and 295.5 µg/mL respectively. The selectivity indexes of W, P, and D were 34, 4, and 91 on WiDr, while HTB 183 was 31, 3, and 7, respectively. The P contained artemisinin, quercetin, kaemferol, and rutin, while the W contained no rutin. The cytotoxicity of both plants was less than doxorubicin. Both plants were selective on WiDR and HTB 183.